Role of Triglyceride to High Density Lipoprotein (TG/HDL) Ratio as A Marker of Insulin Resistance in Adults of Central India: A Narrative Review - Khalid Khan; Sabiha Quazi; Anil Wanjari (Medsci Publications, 2024)
One of the main risk factors for the onset of type 2 diabetes mellitus (T2DM) and cardiovascular diseases (CVD) is insulin resistance (IR). But because there aren't many easy-to-use and trustworthy biomarkers or tests, the entity is frequently under diagnosed. The present review was performed with an aim to provide the available data regarding the role or efficacy of TG/HDL ratio as an indicator of IR in adults of central India, a region popular for high prevalence of T2DM and CVD. An extensive search of all materials related to the topic was carried out in the PubMed search engine. Relevant research articles focusing on use of TG/HDL as a marker of insulin resistance published in the period 2002 to 2023 were included in the review. A total of 33 articles were selected based upon their suitability with the current review objectives and analyzed. The review concludes that TG/HDL ratio is a simple, affordable, and feasible marker of IR that can be used in economically poor regions of the India or world for screening IR and risk stratification of T2DM and CVD in adults. However, more studies are needed in India and all over the world to validate this marker and its cut-off values.